PEMBERDAYAAN KELUARGA SEBAGAI UPAYA PENCEGAHAN HIPERTENSI DI DESA TAWUN KECAMATAN KASREMAN KABUPATEN NGAWI - Yudisa Diaz Lutfi Sandi; Hamidatus Daris Saadah; Rini Komalawati (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2020)
Background: Hypertension is a disease that causes high morbidity and is the main cause of death in almost all developing countries. The lack of information circulating in the community regarding the signs and symptoms of hypertension means that this disease is often referred to as a deadly silent killer without any symptoms as a warning to its victims. The prevalence of hypertension is increasing all the time while the condition of the health workers is limited, so it requires family participation in efforts to prevent hypertension and empower families so that the dangers of hypertension can be understood by the community.Aims: This community service activity is carried out by providing counseling to the community regarding knowledge and skills about preventing hypertension in families in Mencon, Tawun Village, Kasreman District, Ngawi Method: that used was lectures, training, question and answer. Result: Through 14-days hypertension control program, activities carried out of counseling in the community, 3 times of early detection training and prevention of hypertension to the family, 2 times of low sodium salt distribution. Conclusion: Partners are able to find out hypertension prevention efforts, early detection and public health status in Mencon, Tawun Village, Kasreman District, Ngawi.